KRYTYKA TEATRALNA ADAMA GRZYMAŁY-SIEDLECKIEGO - Szczepkowska, Ewa (Acta Neophilologica, 2018)
The article presents the figure of Adam Grzymała-Siedlecki, a forgotten writer, who was a playwright, novelist, biographer, director, manager of Cracow theatre. He was also a theatrical reviewer and a historian and theoretician of the theatre. One of his most important activities was theatre critcism. His attitude to theatre evolved during a few decades. At the begining of the XX century he was impressed by the ideas of the Great Theatre Reform es- pecially those ones represented by Gordon Craig. Polish critic considered theatre as an autonomic art, appreciated the setting for a theatre play and the main role of a director. In interwar period, when he worked as a reviewer in Kurier Warszawski, he became more traditional and conservative: according to him the most important person in the play is an actor. In his reviews he also called for a repertoire based on Polish comedies, realistic dramas and Polish classics. The view that the fundamental value of the theatre is the interaction between the audience and the actors stands him out in the context of the Young Poland theatre criticism.